Nasal colonization with methicillin-resistant Staphylococcus aureus among elderly living in nursing homes in Brazil: Risk factors and molecular epidemiology - da Silveira, Monica [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza [UNESP]; de Souza, Camila Sena Martins [UNESP]; Correa, Adriana Aparecida Feltrin [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (Springer Nature, 2018)
Background: Methicillin-resistant Staphylococcus aureus poses a threat to elderly living in nursing homes. Studies focusing on the epidemiology of colonization may help in the design of infection control strategies. Objective: To identify factors associated with MRSA colonization and the dissemination of clones among nursing home residents. Methods: Nasal swabs were collected from 300 persons from nine nursing homes in the city of Bauru, Brazil. Resistance to methicillin was identified through amplification of the mecA gene. Strain typing (Pulsed-Field Gel Electrophoresis) and characterization of the Staphylococcal Chromosome Cassette (SCC) mec was performed. Univariate and multivariable models were used to identify predictors of overall S. aureus and MRSA carriage. Results: Rates of S. aureus and MRSA colonization were 17.7 and 3.7%, respectively. Age and recent admission to a hospital were independently associated with colonization with S. aureus. MRSA colonization was associated with living in small (< 15 residents) and medium-sized (15-49 residents) facilities, as well as with recent hospitalization. Most MRSA strains carried SCCmec types II or IV, and there was evidence of clonal spread within and among different facilities. Conclusions: MRSA may be introduced in nursing homes form hospitals or arise from the community setting. Screening for asymptomatic colonization may identify persons with greater risk for infection, and is advised for residents discharged from acute care hospitals.
Keywords: MRSA; Nursing homes; Staphylococcus aureus